Balancing Higher Education, Vocational Training, and Lifelong Learning: Evidence on Skills Mismatch and Labor Market Outcomes - Agus Dwi Santoso; Arleiny Arleiny; Eka Wahyu Ardhi; Agus Dwi Santoso; Arleiny Arleiny; Eka Wahyu Ardhi (Universitas Negeri Malang, 2026)
The rapid expansion of higher education has reshaped workforce qualification structures in many countries, yet concerns persist regarding skills mismatch and uneven labor market outcomes. This study examines the implications of imbalances between higher education, vocational education, and lifelong learning for workforce composition and employment outcomes. Using secondary data and comparative evidence from prior empirical studies, this analysis documents substantial growth in higher education attainment while limited expansion of intermediate vocational skills. Results indicate that while higher education graduates generally experience favorable employment outcomes, vocational graduates with strong work-based training demonstrate competitive and sometimes superior long-term trajectories. Participation in adult education and training has increased but remains uneven across age groups and skill levels. Evidence on apprenticeship reforms suggests a shift toward higher-level qualifications and younger participants, accompanied by overall declines in participation. These findings underscore the structural nature of skills mismatch and the limitations of education systems that prioritize academic pathways without providing adequate support for vocational and continuing training. The study contributes to the literature by integrating evidence across education pathways and emphasizing the need for balanced policy approaches to skill formation, workforce adaptability, and inclusive labor market development.